IMPLEMENTASI TEKNOLOGI INFORMASI UNTUK PENGEMBANGAN USAHA BATIK TULIS LASEM - A. Aviv Mahmudi; Riskin Hidayat (Buletin Abdi Masyarakat, 2022)
The COVID-19 pandemic has had a tremendous impact on all sectors, including the MSME sector. Batik Tulis Lasem is one of the superior products of the Rembang Regency area which has been hampered by the impact of the COVID-19 pandemic. Community Service Partners in this activity are the MSME Batik Tulis Lasem. MSME actors are still doing marketing conventionally, they have not been able to maximize information technology. Management of Business Management and Financial Administration is still carried out in a simple manner, there is no clear division of tasks, financial management is not good, there is no proper recording of business transactions. This community service activity aims to provide knowledge and understanding to partners regarding the importance of online marketing and digital marketing information technology for partner businesses; teach the practice of online marketing information technology and digital marketing by utilizing social networks to MSME partners/actors, as well as providing knowledge and increasing understanding of business and financial management. The result of this community service activity is that members of the UMKM Batik Tulis Lasem, Lasem, Rembang realize the importance of business management, especially in the use of Information Technology. Improve business management capabilities, use social media, digital marketing, and Market Place to increase market share. MSMEs also have the ability to manage Android-based financial report records and create digital marketing designs with Canva.